Upaya Realisasi One China Policy melalui ECFA: (Economic Cooperation Framework Agreement) - Arif Ramadhan, M. Syamsul (International Relations Study Program, The Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2021)
Despite many historical similarities, China and Taiwan experience a non-harmonious bilateral relationship. The two countries, which still have political differences, are trying to establish a relationship through the economic aspect. Until the establishment of the ECFA (Economic Cooperation Framework Agreement) which integrates China-Taiwan economic relations. However, researchers see that this is not only economical aspect, but also China’s effort to realize One China Policy. This study seeks to explore Chinese government efforts to realize One China Policy through ECFA. To convey a proper analysis, this study uses the concept of Commercial Diplomacy. By using a qualitative approach and documentation techniques to collect data, the data were analyzed using Milles and Huberman's data analysis techniques. Researchers found some evidence that; The ECFA leads to the realization of the One China Policy. It is evident from the four categories of efforts by the Chinese Government to realize ECFA, namely in the fields of intelligence, networking and public relations, implementation contract negotiators, and problem solving.